Capacidade estatal: diagnóstico da implementação da política pública de economia solidária no Estado da Paraíba - Mélo, Heverton Felinto Pedrosa de (2020)
This research analyzes the Solidarity Economy as an instrument of public development policy. For this, an exploratory study was carried out through documentary and field research. The approach adopted was qualitative. It is verified how the implementation process of the public policy of solidary economy in the State of Paraíba occurs, as a strategy for a better quality of life of the citizens. The main configurations and institutional design adopted by government management are demonstrated in order to achieve a possible way of overcoming social, economic and political inequalities. The scientific method used in the research enabled the theoretical debate and the survey of empirical data on the actors studied, as well as the identification of the factors that facilitated or hindered the implementation of that policy. From this, a diagnosis was made that took into account the dimensions of the nature of the policy, policy design and policy management. The purpose of this study was to leverage this governmental agenda in the territory of Paraíba, revealing the level of state capacity of the state management. A brief history of the Solidarity Economy in Brazil is addressed, including its concept, principles and developments. The types of actions adopted for structuring the Executive Secretariat for Solidarity Economy and the management model practiced in the conduct of this public policy in Paraíba are highlighted, highlighting the existing public facilities. It emphasizes the context of the creation of the State Plan, the main rules in force and the performance of the State Executive Branch in consolidating the solidarity economy agenda. The main barriers and challenges faced by public managers in the conduct of this policy are revealed. It is pointed out in the results that the analyzed factors directly influenced the state's performance, mobilizing its technical-administrative and political-relational capacities. The study revealed that the disarticulation between the variables that make up the dimensions examined represented obstacles to the implementation of the solidarity economy policy in Paraíba, but that despite the limits, that policy also advanced.